Creation of organizational-functional and economic models of the university (Journal of Economic Research & Business Administration, 2018)
In the conditions of formation of innovative economy, the main factor of development of subjects ofthe economy is the intellectual potential.The change in the role of knowledge in social and economic development requires a fundamentalchange in the function of the social institution of education in the material and spiritual reproduction ofthe living conditions of society and man.The combination of the capabilities of individual subjects and scientific and pedagogical teamsin the implementation of educational, scientific and innovative activities determines the intellectualpotential of higher education institutions, and contributes to the development and formation of an effectiveinvestment policy at individual enterprises, organizations and institutions. One of the main tasks ofregional development and the country as a whole is the creation and development of such an organizationaland functional model of the university that would allow managing the adaptation of education andscience in the emerging competitive environment. It is in such an environment, under the influence ofinternal and external factors, the intellectual potential of a modern university, in the unity of its cultural,educational, scientific and innovative componentsThe mechanism for managing the intellectual potential of universities should be based on the interactionof external and internal factors of their current activities that affect the competitiveness of educationalinstitutions of higher professional education in the market of educational services.